A discourse analysis in articles about agricultural products in english and vietnamese (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Base on the theories of Discourse Analysis, this thesis makes a Discourse Analysis of Articles about Agricultural Products in English and Vietnamese in order to discover some typical discourse features and find out the similarities and differences between them in term of the layout, lexical features and cohesive features. The findings of this study are presented based on a survey of 50 article items in English and 50 one items in Vietnamese newspapers which are taken well-known websites. It is hoped that the results of this study will really provide some practical applications for teaching and learning English. This thesis may also be helpful for students as well as reporters in writing successful articles about agricultural products.